Persia in Early Modern English Drama, 1530–1699 - Houston, Chloë. author. aut Link
XII, 295 p. 1 illus.
Keywords: This book is a study of the representation of the Persian empire in English drama across the early modern period, from the 1530s to the 1690s. Its wide focus, encompassing fifteen dramatic entertainments, both canonical and little-known, allows it to trace the changes and developments in the dramatic use of Persia and its people across the period. It explores what Persia signified to English playwrights and audiences in this period; ideas and associations conjured up by mention of ‘Persia’; and where information about Persia came from. It also considers how ideas about Persia changed with the development of global travel and trade, as English people came into contact with Persians for the first time. In addressing these issues, this book provides an examination not only of the representation of Persia in dramatic material, but of the broader relationship between travel, politics and the theatre in early modern England. Chloë Houston is Associate Professorin the Department of English Literature at the University of Reading, UK. .